Opposite serotonergic modulation of sharp waves in the dorsal and ventral hippocampus - Kandilakis, Charalampos L.; Papatheodoropoulos, Costas (Frontiers in Synaptic Neuroscience, 2025)
Serotonin plays a crucial role in regulating hippocampal network dynamics, however, its effects on sharp wave–ripples (SPWs), a pattern fundamental for memory consolidation and emotional processing, remain incompletely understood, particularly along the dorsoventral axis. Using hippocampal slices from adult rats, we compared serotonergic modulation of SPWs and associated multiunit activity (MUA) in dorsal and ventral CA1 regions. Serotonin (1–100 μM) was applied to evaluate dose dependent and region-specific effects on SPW amplitude, duration, frequency, and neuronal firing. We found that serotonin reduces SPW amplitude in both hippocampal segments, decreases the rate of SPW occurrence in the dorsal hippocampus, and increases the rate of SPW occurrence in the ventral hippocampus, but only at relatively low concentrations. The suppressive effect on SPW amplitude is accompanied by a reduction in firing frequency during SPWs in both regions, whereas the enhancing effect of low serotonin concentrations on SPW rate in the ventral hippocampus is associated with an excitatory action on basal neuronal activity. These results reveal a region-specific, and dose-dependent serotonergic modulation of SPWs, reflecting distinct excitatory/inhibitory balances and receptor subtype distributions along the hippocampal axis. Functionally, serotonergic suppression of dorsal SPWs may regulate cognitive processes, whereas bidirectional modulation in the ventral hippocampus may fine-tune affective and stress-related responses. Our findings highlight dorsoventral specialization of serotonergic control over hippocampal network patterns, providing insights into the mechanisms of dorsoventral hippocampal specialization and the symptom heterogeneity of neuropsychiatric disorders involving serotonergic dysfunction.